2013
DOI: 10.1680/macr.13.00190
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GO on cement hydration crystals and its toughening effect

Abstract: An aqueous dispersion of graphene oxide (GO) nanosheets with different oxygen content was obtained from graphite via oxidation and ultrasonication. The effects of GO nanosheets on the microstructure and mechanical properties of hardened cement paste were determined by scanning electron microscope, X-ray diffractometer and tensile/flexural/compressive strength investigations. The results indicate that GO nanosheets can regulate the formation of flower-like crystals and distinctly improve the tensile, flexural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(41 citation statements)
references
References 23 publications
0
39
0
2
Order By: Relevance
“…5a [18]. This phenomenon has been observed by other researchers as well [25]. Other researchers Panzavolta [26] have stated that graphene and graphene oxide based composites fabrication has a major issue of restacking graphene sheets because poor interaction with the matrix.…”
Section: Accelerated Chloride Penetrationmentioning
confidence: 66%
“…5a [18]. This phenomenon has been observed by other researchers as well [25]. Other researchers Panzavolta [26] have stated that graphene and graphene oxide based composites fabrication has a major issue of restacking graphene sheets because poor interaction with the matrix.…”
Section: Accelerated Chloride Penetrationmentioning
confidence: 66%
“…We would like to mention here that from visual inspection and UV-vis spectra, it was found that the GO sheets were well dispersed in aqueous solution even after 2 h. (b) Bond formation between cement matrix and GO sheets: The increase in compressive strength of GO-cement composite could be endorsed to the strong bond between the cement matrix and GO. The surface of GO contains many oxygen functional groups -OH and -COOH, which form a strong covalent bond with C-S-H and CH [53,54]. The presence of the chemical interaction was also observed in the FTIR spectra and TGA/DTA data.…”
Section: Compressive Strength Of Cement Based Compositesmentioning
confidence: 82%
“…9). The microstructure is changed with the increasing GO dosages, which is explained in Lv's research [18,19].…”
Section: Effect Of Go Sf and Gosf On The Mechanical Properties Of Cementioning
confidence: 91%
“…Consequently, GO shows a better gain in compressive strength at a lower concentration when compared to CNT reinforced cement [12]. The introduction of GO in cement not only can regulate hydration but also improve the tensile, flexural and compressive strengths of the cement paste [8,[18][19][20][21][22]. Lv et al [19] discovered that when the content of GO was 0.03%, the cement composites exhibited remarkable increase in tensile strength (78.6%), flexural strength (60.7%) and compressive strength (38.9%).…”
Section: Introductionmentioning
confidence: 99%